Daptomycin in the treatment of prosthetic joint infection by Enterococcus faecalis: safety and efficacy of high-dose and prolonged therapy - José Ramón Yuste; Milena Quesada; Pablo Díaz-Rada; José Luis Del Pozo (International Journal of Infectious Diseases, 2014)
Enterococci are implicated in less than 2.3% of prosthetic joint infections. These infections can be difficult to treat and therapeutic failures are not uncommon. In these situations, daptomycin is a safe and effective alternative. We present a clinical case with a successful response to the prolonged use of high-dose daptomycin.